Fairness views and political preferences: Evidence from a representative sample - Daniel Müller; Sander Renes (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We elicit distributional fairness ideals of impartial spectators using an incentivized elicitation in a large and heterogeneous sample of the German population. We document several empirical facts: i) egalitarianism is the predominant ideal; ii) females are more egalitarian than men; iii) men are relatively more efficiency minded; iv) left-leaning voters are more likely to be egalitarians whereas right-leaning voters are more likely to be efficiency minded; and v) young and highly-educated participants hold different fairness ideals than the rest of the population. Moreover, we show that the fairness ideals predict preferences for redistribution and intervention by the government, as well as actual charitable giving, even after controlling for a range of covariates. Hence, our paper contributes to our understanding of the underpinnings of voting behavior and ideological preferences, as well the literature that links lab and field behavior.
Keywords: C90; D31; D63; 330; Distributional fairness; impartial spectator; representative sample; political attitudes; voting behavior; lab to field